BK virus in kidney transplant recipients with graft dysfunction. Issue 1 (31st December 2023) - Riad, Doaa Mohamed; Mowafy, Wafaa Kamel; Saleh, Hazem Hamed; El Sawy, Essam Mahmoud; Abou El-Khier, Noha Tharwat
ABSTRACT: This study was to estimate the viral load of BK virus (BKV) in the urine and blood of Kidney transplant recipients (KTRs) with graft dysfunction and its effect on the development of graft dysfunction. This analysis included all KTR outpatients who visited the clinic at Urology and Nephrology Center during their routine follow-up visits from September 2017 to May 2019. A total of 100 patients were divided into 62 KTR patients with kidney dysfunction (case group) vs. 38 KTR patients without kidney dysfunction (control group). BKV DNA quantification in urine and plasma samples was examined in all patients by the real time PCR method. The BKV DNA was detected in the urine samples of 5 patients, all with kidney dysfunction (8%) vs. none in the control group. The BKV viral load of the 5 cases ranged from 105 to 244000 copies/ml. The BKV DNA was not detected in the blood samples of the 5 urine-positive cases. It was concluded that all patients with kidney dysfunction should be screened for BKV in their urine samples to prevent the development of BKV-caused nephropathy and further graft failure.